Analysis of Factors Influencing the Gender Empowerment Index in Central Java - Gandes, Gradeletta Prima; Utomo, Yuni Prihadi (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the influence of the Female Labor Force Participation Rate (FLFPR), Percentage of Women Who Have Ever Accessed the Internet (PPMI), Percentage of Female Population, Average Years of Schooling (AYS) for women, and Female School Participation Rate (SPR) on the Gender Empowerment Index (GEI) in Central Java Province during the period 2019–2023. This research employs a quantitative approach using secondary data and applies panel data regression analysis through the Fixed Effect Model (FEM). The results show that PPMI has a significant positive effect on GEI, while FLFPR, Percentage of Female Population, AYS for women, and SPR do not have a significant effect. The insignificant variables indicate that improvements in formal education, the proportion of the female population, and labor force participation alone are insufficient to substantially enhance gender empowerment. Conversely, PPMI emerges as a key factor, as internet access broadens women’s opportunities to acquire information, skills, and networks, thereby increasing their capacity, participation, and bargaining power in economic, political, and social spheres, and serving as a strategic catalyst for accelerating gender empowerment policies at the regional level.